2008
DOI: 10.14203/mri.v33i1.506
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbonoclastic Bacteria From Jakarta Bay and Seribu Islands

Abstract: Jakarta Bay has been known as one of the most polluted marine environment in Indonesia, with no exception by oil. Seribu Islands waters, located in the north of Jakarta Bay may have been impacted by this polluted condition.It’s sometimes also hit by oil spillage from pipe leakage. The purpose of this study is to isolate and identify hydrocarbonoclastic bacteria (oil and Polyaromatic Hydrocarbon degrading bacteria) from Jakarta Bay and Seribu Island waters. The bacteria were isolated from water and sediment/san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition, Darmayati et al . [ 17 ] isolated Pseudidomarina sp. from oil polluted marine sediments but no PAH degrading abilities were reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Darmayati et al . [ 17 ] isolated Pseudidomarina sp. from oil polluted marine sediments but no PAH degrading abilities were reported previously.…”
Section: Discussionmentioning
confidence: 99%
“… 69 Moreover, this genus was identified among the hydrocarbonoclastic bacteria isolated from Jakarta Bay and Seribu Islands that are known as the most polluted marine environment in Indonesia. 70 In addition, a recent study showed the increase of Alcanivorax genus during the remediation of crude oil-polluted soil by bacterial rhizosphere community. 71 Moreover, Alcanivorax borkumensis which is a marine alkane-degrading bacterium harbors enzymes involved in alkane oxidation (cytochromes CYP153 and AlkB homologs which are well-characterized particulate membrane-bound hydroxylase).…”
Section: Discussionmentioning
confidence: 99%
“… 69 Furthermore, this genus was isolated from oil polluted marine sediments in Indonesia. 70 Moreover, indigenous Pseudidiomarina from mangrove surface sediments of Nay band Bay in Iran showed high potential to degrade fluorene and phenanthrene. 76 In our study, Pseudidiomarina genus showed abundance at T9 simultaneously with an enduring high level of phenanthrene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomolecular approaches have been used for the isolation and identification of oil-degrading bacteria in Indonesia since 2005. Darmayati et al. (2008) isolated 131 different hydrocarbonoclastic bacterial strains from Jakarta Bay and Seribu Island.…”
Section: Introductionmentioning
confidence: 99%